Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1021/es050165d
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gold Catalyst for Mercury Oxidation by Chlorine

Abstract: This paper discusses a recent study of mercury catalytic oxidation by chlorinating reagents. Gold was chosen as the catalyst because of its reluctance to chemisorb some gases such as O2, NO, H2O, and SO2. This property, as demonstrated in this study, is instrumental to mercury oxidation by circumventing some undesired inhibitory reactions such as OH + NO + M --> HONO + M and OH + SO2 + M --> HOSO2 + M, which were recognized under homogeneous situations at high temperatures. In comparison to Cl2, HCl showed wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
96
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 28 publications
7
96
2
Order By: Relevance
“…The oxidation of Hg in the flue gas occurs mainly by chlorinating species 2,11,12 such as HCl in the postcombustion environment, in which its concentration is on the order of hundreds of ppm, several orders of magnitude greater than Hg, which is on the order of ppb levels. 11 The interaction between Au and Cl has been widely investigated previously.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of Hg in the flue gas occurs mainly by chlorinating species 2,11,12 such as HCl in the postcombustion environment, in which its concentration is on the order of hundreds of ppm, several orders of magnitude greater than Hg, which is on the order of ppb levels. 11 The interaction between Au and Cl has been widely investigated previously.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the reduction in Hg 0 concentration and the increase in O 3 concentration in the PCD process as a function of the input energy density, where the O 2 and H 2 O content were set to 10% and 3% in N 2 . At an input energy density of 45 J / l, the Hg 0 concentration dropped from 45 to 7 g / m 3 , an oxidation efficiency of 84%. This shows that Hg 0 oxidation is possible in a NTP process.…”
mentioning
confidence: 99%
“…3͑b͒ where an increasing amount of SO 2 is added to the gas flow without addition of NO. It may be seen that unlike NO, SO 2 3 and O but also Cl and Cl 2 can be strong oxidants for Hg 0 in the PCD process. In the plasma process, it is expected that HCl in the gas stream will be dissociated by direct collision with energetic electrons and excited nitrogen molecules, resulting in Hg 0 oxidation to HgCl 2 by the following reactions ͑3͒-͑8͒.…”
mentioning
confidence: 99%
“…For instance, Cl might be produced when NaCl particles are present. As one of the most common composition in flue gas from coal combustion (Saarnio et al, 2014), Cl has been reported for rapidly reacting with Hg 0 in gas phase and on the particle surface to form oxidized mercury (Zhao et al, 2006;An et al, 2014). Possibly due to this mechanism, NaCl aerosol performs better in improving Hg 0 removal than sucrose aerosol.…”
Section: Possible Mechanisms For Improving Mercury Removal In the Ddbmentioning
confidence: 99%
“…Many technologies have been developed for mercury control (Biswas et al, 1999), such as injecting powdered activated carbon to adsorb mercury (Sjostrom et al, 2010;Clack, 2012), injecting halogen reagents (Zhao et al, 2006) and using UV light and ozone to realize mercury oxidization (Wu et al, 1998;Granite and Pennline 2002;Lee et al, 2004;McLarnon et al, 2005;Wang et al, 2007;Yang et al, 2012). Non-thermal plasma operated at atmospheric pressure is one of the promising technologies for converting gaseous elemental mercury (Hg 0 ) to oxidized mercury (Hg 2+ ) and particulate bound mercury (Hg p ) (Chen et al, 2006;Byun et al, 2011a), which can then be effectively removed by conventional air-pollution control devices (Clack, 2006).…”
Section: Introductionmentioning
confidence: 99%